Aku Bisa Makan dengan Santun - Natasya Virginia Leuwol; Sherly Gaspersz; Aaron William Samallo; Maria Enjelina Letlora; Ria Akihary (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This Community Service Program (PKM) was conducted as an effort to support the development of positive habits among children at Bukit Hermon Orphanage in Sorong City. The program adopted the theme “I Can Eat Politely” and aimed to provide children with an understanding of proper and appropriate eating habits while encouraging politeness, self-confidence, and enthusiasm for learning. An educational and participatory approach was applied through material delivery, quizzes, ice-breaking activities, motivation sessions, and group interaction. The activity was conducted on July 3, 2026, involving university students, a supervising lecturer, orphanage administrators, and children. The results showed that the program was implemented successfully, with children demonstrating enthusiasm and active participation in educational activities, quizzes, games, and discussions. The program provided positive educational and social experiences for the participants while strengthening students’ social awareness, communication, teamwork, and responsibility. Similar programs should be implemented continuously with more measurable evaluation instruments.